2005
DOI: 10.1139/t05-040
|View full text |Cite
|
Sign up to set email alerts
|

Development and verification of a numerical model for the analysis of geosynthetic-reinforced soil segmental walls under working stress conditions

Abstract: The paper describes a numerical model that was developed to simulate the response of three instrumented, full-scale, geosynthetic-reinforced soil walls under working stress conditions. The walls were constructed with a fascia column of solid modular concrete units and clean, uniform sand backfill on a rigid foundation. The soil reinforcement comprised different arrangements of a weak biaxial polypropylene geogrid reinforcement material. The properties of backfill material, the method of construction, the wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 285 publications
(132 citation statements)
references
References 24 publications
6
121
0
5
Order By: Relevance
“…Ling and Leshchinsky [5], Hatami and Bathurst [7,8] and Guler et al [9] verified their numerical models against carefully constructed, instrumented and monitored walls. Reviews of numerical modelling of geosynthetic reinforced soil wall can be found in the papers by Bathurst and Hatami [10] and Ling [11].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Ling and Leshchinsky [5], Hatami and Bathurst [7,8] and Guler et al [9] verified their numerical models against carefully constructed, instrumented and monitored walls. Reviews of numerical modelling of geosynthetic reinforced soil wall can be found in the papers by Bathurst and Hatami [10] and Ling [11].…”
Section: Introductionmentioning
confidence: 92%
“…8 Comparison of stress-strain curves of WGT reinforced sand (RD-40 %, r 3 -50 kPa) based on equivalent and discrete approach Fig. 9 Comparisons of stress-strain curves of WGT reinforced sand (RD-40 %, r 3 -50 kPa) using Mohr-Coulomb and Duncan-Chang model scale geogrid reinforced retaining wall constructed at Royal Military College of Canada (RMC) [7,8] and a reinforced retaining wall problem analysed by Guler et al [9] were analysed using FLAC. The equivalent numerical model is systematically verified with the instrumented data together with results from discrete approach.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include stabilization of highway slopes and embankments [4], and reinforcement of foundations [5,6], and paved and unpaved roads [7][8][9] in order to mitigate cracking and rutting, prolong service life and reduce aggregate base course thickness for a given traffic volume.…”
Section: Geogrids: Types and Applicationsmentioning
confidence: 99%
“…Yazdani et al [27] modified a standard direct shear test apparatus and used it to investigate the influence of confining pressure on the tensoresistive response of PVC-coated PET yarn SEGG. They carried out their in-soil tensile tests at three different confining pressures of 10, 30 and 50 kPa to represent upper levels of reinforced soil structures where larger deformations typically occur [4]. It was found that greater confining pressures and strain rates both reduce the tensoresistivity of SEGG samples (Fig.…”
Section: Segg's State Of Developmentmentioning
confidence: 99%